Toma de conciencia sobre los trastornos específicos del lenguaje: la campaña RALLI en Internet - Conti-Ramsden, G; Bishop, D; Snowling, M; Clark, B; Norbury, C (2013)
In this editorial, we discuss what is specific language impairment (SLI) and why it is a hidden disability that few people have heard about. We describe the impact on research, policy and practice of SLI being a neglected condition. We end by providing the background and rationale of a new internet campaign, RALLI (www.youtube.com/rallicampaign), aimed at changing this state of affairs and raising awareness of SLI. This YouTube channel has videoclips and information about SLI in Spanish. © 2013 AELFA.